PRESSURE-IMPACT ANALYSIS OF THE COASTAL WATERS OF MARMARA SEA - Tan, Ibrahim; Beken, Colpan Polat; Oncel, Salim (Parlar Scientific Publications (P S P), 2017)
The European Union Water Framework Directive (WFD) recommends the pressure and impact analyses as a risk evaluation method for achieving the ecological quality targets. The aim of the present study is to determine potential risks on the coastal water bodies (WB) of the Marmara Sea considering different anthropogenic pressures. Land Uses Simplified Index (LUSI); and Land Uses Simplified Index Valencia (LUSIVal) were applied to 18 coastal water bodies of Marmara Sea. Correlations between LUST, LUSTVal indices and chlorophyll-a, as the impact variable indicating the phytoplankton biomass, were calculated as R2 = 0.14, p <0.067 and R-2= 0.54; p<0.0004, respectively. Hence, the results of LUSIVal index were found to be more applicable for Marmara Sea. A comparison of both methods were also conducted. Both indices have certain limitations; LUSI is only based on Corine land classification system whereas LUSIVal also includes certain pressures like rivers, pollution and bays as risk factors. Still LUSIVal method is not considering all the pressure factors; e.g. those associated directly with sea, tourism and animal husbandry. The LUSI/LUSIVal index was also found to be not appropriate for evaluation of the ecological status of all coastal water bodies. This might be due to the response of the systems to natural variability rather than the pressures. In addition, other biological quality elements (macro flora and fauna) were considered besides chlorophyll-a in ecological quality assessments and further efforts to correlate pressure indices with other impact variables might be recommended for future assessments.
Keywords: Water Framework Directive; coastal waters; pressures-impacts; LUSI/LUSIVAL; Marmara Sea